Effects of shunt types used in idiopathic normal pressure hydrocephalus on patients’ clinical outcomes (Annals of Medical Research, 2023)
Aim: Idiopathic normal pressure hydrocephalus (iNPH) is a surgically reversible neurological disease in adults. It is a neurological condition characterized by ventricular enlargement detected on cranial imaging as well as gait defect, cognitive reduction, and urinary incontinence, with no other reason to explain the clinical findings. Ventricular shunting, predominantly ventriculoperitoneal (VP) shunting, has been shown to be successful in relieving symptoms in patients. In this study, we aimed to investigate the effects of two VP shunts used in the iNPH patients treated in our clinic.Materials and Methods: Clinical and laboratory records of 28 patients who underwent VP shunting due to iNPH were reviewed retrospectively via the Enlyl system. A programmable shunt was inserted in 9 (32.1%) and a medium-pressure shunt was inserted in 19 (67.9%) patients.Results: There was no significant difference between the two shunt types with regard to patient age, gender, and preoperative tests (p>0.05). However, the prevalence of ataxic gait was significantly higher in the Programmable Shunt group compared to the Medium-Pressure Shunt group (p0.05 for both).Conclusion: In the present study, no significant difference was observed between the shunt types with regard to clinical outcomes and thus both types of shunts were revealed as viable options.
Keywords: Normal-pressure hydrocephalus; Ventriculoperitoneal shunt; Programmable shunt; Medium-pressure shunt